A President’s Perspective on EDUCAUSE’s Grand Challenges - Hrabowski III, Freeman A. (My University, 2007)
This past year, EDUCAUSE President Brian Hawkins identified three “grand challenges” facing higher education: access, affordability, and accountability. I’d like to share my perspective, as a university president, on two of these challenges, as well as a third: assessment. I’d also like to suggest how technology can help to address these grand challenges